2009
DOI: 10.1002/hep.22683
|View full text |Cite
|
Sign up to set email alerts
|

Missense mutations and single nucleotide polymorphisms in ABCB11 impair bile salt export pump processing and function or disrupt pre-messenger RNA splicing #

Abstract: The gene encoding the human bile salt export pump (BSEP), ABCB11, is mutated in several forms of intrahepatic cholestasis. Here we classified the majority (63) of known ABCB11 missense mutations and 21 single-nucleotide polymorphisms (SNPs) to determine whether they caused abnormal ABCB11 pre-messenger RNA splicing, abnormal processing of BSEP protein, or alterations in BSEP protein function. Using an in vitro minigene system to analyze splicing events, we found reduced wild-type splicing for 20 mutations/SNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
154
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(165 citation statements)
references
References 63 publications
(145 reference statements)
8
154
3
Order By: Relevance
“…Therefore, individuals with the 1331CC genotype had an ABCB11 expression of 80% compared with those harboring the 1331TT genotype. Our in vitro study reinforced the results of Byrne et al (2009) and Meier et al (2006) and identified decreased protein stability as a cause of reduced protein expression. Although some missense mutations, such as the D482G, enhanced aberrant splicing shown using a minigene system, this SNP (1331T.C) did not alter the pre-mRNA splicing pattern (Byrne et al, 2009).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Therefore, individuals with the 1331CC genotype had an ABCB11 expression of 80% compared with those harboring the 1331TT genotype. Our in vitro study reinforced the results of Byrne et al (2009) and Meier et al (2006) and identified decreased protein stability as a cause of reduced protein expression. Although some missense mutations, such as the D482G, enhanced aberrant splicing shown using a minigene system, this SNP (1331T.C) did not alter the pre-mRNA splicing pattern (Byrne et al, 2009).…”
Section: Discussionsupporting
confidence: 86%
“…Our in vitro study reinforced the results of Byrne et al (2009) and Meier et al (2006) and identified decreased protein stability as a cause of reduced protein expression. Although some missense mutations, such as the D482G, enhanced aberrant splicing shown using a minigene system, this SNP (1331T.C) did not alter the pre-mRNA splicing pattern (Byrne et al, 2009). A major concern is whether a 444A protein with slightly reduced transport activity can cause acquired cholestasis.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…PFIC2 is a consequence of mutations in the gene encoding the human bile salt export pump (BSEP, ABCB11; rodent ortholog Bsep, Abcb11; originally termed "sister of P-glycoprotein," spgp), which mediates efflux of bile salts from hepatocytes into bile and is essential for normal bile formation and flow. In patients with PFIC2, mutations or single nucleotide polymorphisms (SNPs) in the BSEP gene result in either reduced levels of mRNA transcription or translation or reduced protein stability or activity (Strautnieks et al, 2008;Byrne et al, 2009;Ho et al, 2010), and liver injury is considered to be caused by intracellular accumulation of cytotoxic bile constituents (Perez and Briz, 2009). Less functionally severe ABCB11 gene mutations have been shown to result in benign recurrent intrahepatic cholestasis type 2, which is characterized by nonprogressive cholestasis (Noe et al, 2005).…”
Section: Introductionmentioning
confidence: 99%